Localization of Light in Photonics Lattices for All-Optical Representation of Binaries - Nguyen, Dan T.; Nolan, Daniel A.; Borrelli, Nicholas F. (Frontiers in Physics, 2021)
Optical computing, in theory, possesses myriad advantages and represents a massive improvement over current electrical computing. However, despite decades of effort and progress made in related technologies, the goal of an all-optical digital computer has remained largely unfulfilled. One of the reasons for this failure is that the key components that can optically perform the representation of binary and arithmetic operations have been unsuccessful for computing. Specifically, searching for materials of high optical nonlinearity to provide low energy optical switches for developing integrated on-chip, all-optical binary representation components has not been successful. Here, we present a novel method for all optical representation of binary numbers that could be used for all-optical binary logic components in optical digital computing, as well as for other applications. The new concept is based on effect of localization of light in specially designed binary photonics lattices. The proposed structures can be made with integrated photonics on-chip that are highly programmable and controllable. Most significantly, the working principle of the novel method doesn’t require nonlinear interaction between light and material, which is the most serious obstacle in the conventional method that uses optical transistors whose mechanism relies mainly on optical nonlinearity. We will discuss some technical challenges in developing the components.